2016
DOI: 10.1186/s12284-016-0103-8
|View full text |Cite|
|
Sign up to set email alerts
|

Lodging Resistance of Japonica Rice (Oryza Sativa L.): Morphological and Anatomical Traits due to top-Dressing Nitrogen Application Rates

Abstract: BackgroundLodging in rice production often limits grain yield and quality by breaking or bending stems. Excessive nitrogen (N) fertilizer rates are the cause of poor lodging resistance in rice, but little is known about the effect of top-dressing N application rates on the mechanical strength of japonica rice plants, especially how the anatomical structure in culms is affected by N. In this study, field experiments on two japonica rice varieties with three top-dressing N application rates, 0 kg N ha−1 (LN), 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 40 publications
8
80
1
3
Order By: Relevance
“…Most of the findings from previous studies are in line with our findings that basal internode length is responsible for higher plant height, which ultimately reduces bending strength of cereals (Zhang et al, 2017a). The results of Zhang et al (2016), which are in agreement with our findings, reported that higher application of N increased the internodes length in rice (Oryza sativa) and resulted in lodging.…”
Section: Plant Heightsupporting
confidence: 92%
“…Most of the findings from previous studies are in line with our findings that basal internode length is responsible for higher plant height, which ultimately reduces bending strength of cereals (Zhang et al, 2017a). The results of Zhang et al (2016), which are in agreement with our findings, reported that higher application of N increased the internodes length in rice (Oryza sativa) and resulted in lodging.…”
Section: Plant Heightsupporting
confidence: 92%
“…Xylem is a transport tissue and also the support structure of plants. Studies have shown that xylem area and xylem proportion are remarkably positively correlated with lodging resistance [30], while pith area and pith proportion are negatively correlated with lodging resistance [31]. Therefore, we measured these indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, high N fertilization resulted in a reduction in the thickness of the secondary cell wall as well as major biopolymer components (cellulose and lignin) in two japonica rice cultivars [57]. Interestingly, agronomically reducing the N fertilization rate can effectively increase plant lodging resistance, which is associated with changes in stem lignification and secondary cell wall synthesis and also emphasizes the negative correlation between N availability and plant epidermal hardness [58,59].…”
Section: Physical Defence Mechanismsmentioning
confidence: 99%